Now I am Become Death”: Japanese and Canadian Industrial Contamination in Michiko Ishimure’s Paradise in the Sea of Sorrow: Our Minamata Disease and Thomas King’s The Back of the Turtle - Ganz, Shoshannah (Canada and Beyond: A Journal of Canadian Literary and Cultural Studies, 2018)
Canada and Japan share a history of industrial contamination that has resulted in mercury poisoning; the inhabitants of both Minamata, Japan and the Indigenous community of Grassy Narrows, Ontario have suffered from what would come to be known as Minamata disease. Environmental activists, proponents of industrial progress, individuals in the affected communities, and novelists Michiko Ishimure and Thomas King discuss and weigh the possibilities of economic and material progress against the problems of environmental degradation and industrial contamination leading to disease and death for humans and ecosystems. This paper will show how Ishimure and King discuss the possibility of hope and renewal through the tourist industry, but will also question the efficacy of “dark tourism.” Is it possible to balance an ethics of care and respect for those whose lives have been destroyed by industrial contamination with the need of those who remain to make a living through tourism? This paper will explore the fictional possibility offered by King alongside the actual recovery and tourist industry generated in the aftermath of the Minamata poisoning and subsequent clean up efforts. Is it possible to reimagine and reclaim industrial wreckage as sites of pleasure and recreation? Do these regenerated sites of industrial destruction promote the common good or further victimize the individuals and communities destroyed in the name of progress?